2021
DOI: 10.1016/j.ejpb.2021.07.016
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of three mucus-secreting airway cell lines (Calu-3, SPOC1 and UNCN3T) for use as biopharmaceutical models of the nose and lung

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 88 publications
0
3
0
Order By: Relevance
“…Thus, the lower TEER values in the static permeation studies resulted in higher permeation coefficients. The impact of the TEER value on the permeation coefficient of FD4 (fluorescein isothiocyanate dextran with an average molecular weight of 4000 Da) on mucus-secreting airway cell lines has been reported by Lee et al [51].…”
Section: Permeation Coefficient For Fitc-dextran 4000mentioning
confidence: 84%
“…Thus, the lower TEER values in the static permeation studies resulted in higher permeation coefficients. The impact of the TEER value on the permeation coefficient of FD4 (fluorescein isothiocyanate dextran with an average molecular weight of 4000 Da) on mucus-secreting airway cell lines has been reported by Lee et al [51].…”
Section: Permeation Coefficient For Fitc-dextran 4000mentioning
confidence: 84%
“…3 F). Several gene expression studies have reported the expression of both MUC5AC and MUC5B in Calu-3 cells ( Gupta et al, 2019 ; Lee et al, 2021 ). Sonntag et al (2022) assessed mucus production in Calu-3 cells by evaluating the level of MUC5AC formation.…”
Section: Resultsmentioning
confidence: 99%
“…This study examined the effect of the corticosteroid, FF on mucus secretion. Despite agreement on the need to investigate the long-term effects of IN steroids on the nasal mucosa, research to date has reported significant improvement of compromised mucociliary function in patients with allergic rhinitis (Hofmann et al, 2004;Houtmeyers et al, 1999a;Klossek et al, 2001;Lee and Gendeh, 2003;Naclerio et al, 2003;Verret and Marple, 2005). However, little is known of the effect of corticosteroid IN formulations on airway mucin secretion.…”
Section: Discussionmentioning
confidence: 99%
“…The use of mucin-secreting cell culture models is an area of research that bears much potential (Lechanteur et al, 2018). Both human bronchial epithelial primary cells (Abdullah et al, 2012) (Hill and Button, 2012;Kemp et al, 2004) and cell lines e.g., UNCN3T, Calu-3 and SPOC1 (rat) have successfully demonstrated mucin secretion (Abdullah et al, 2003;Abdullah and Davis, 2007;Abdullah et al, 1996;Fulcher et al, 2005;Lee et al, 2021;Randell et al, 1996). However the culture and differentiation procedures for primary cultures are labour-intensive and cell lines rarely express motile cilia.…”
Section: Intranasal (In) Administration Provides a Non-invasive Route...mentioning
confidence: 99%